Germinação, morfologia e análise da distribuição espacial da qualidade fisiológica de sementes de Joannesia princeps Vell - Beltrame, Rômulo André (2013)
The success in production of seedlings of forest species is directly related to physiological quality of seeds used. This study aimed to obtain information about the spread of cutieira (Joannesia princeps) and physiological quality of seeds, besides studying aspects morphological and biometrical of fruits, seeds and seedlings. Initially, the objective this work was evaluate physical and chemical treatments and shading levels in the germination and initial development of cutieira seedlings. Intact seeds (T1) and with integument cracked (T2) were evaluated as water absorption. The seeds were subjected to pre-germination treatments: (T1) intact seeds (control), (T2) with seed coat cracked, (T3) with the seed coats removed, (T4) immersion at sulfuric acid (95%) for 5 minutes, (T5) immersion at sulfuric acid (95%) for 10 minutes, (T6) immersion at sulfuric acid (95%) for 15 minutes. Subsequently, we evaluated the relationship between soaking treatments with GA3 at different times (zero, six, 12 and 24 h), and shading (full sun, with one and two shade screens ) on emergence and seedling development. We evaluated: emergency, emergency speed index, shoot length and root, diameter of the base, fresh and dry weight of shoot and root system. Still, aspects morphological and biometrical of fruits, seeds and seedling of Joannesia princeps. In fruits were evaluated qualitative attributes relative to external morphology. The biometric analysis was based having with base the dimensions the length, diameter and thickness. The seeds were evaluated in attempt to external and internal morphology. The seedling assessments were conducted periodically in the sixth, seventh, 14th, 21th, 28th, 35th and 42th day. We used 15 normal and healthy seedlings for descriptions. Lastly, the objective was to study and analyze the spatial distribution on the attributes that determine the physiological quality of seeds Joannesia princeps. Seeds were collected, individually, 40 mother trees in the Horto City Alegre-ES and experiment conducted in the greenhouse of the Department of Plant Production CCAUFES. The seeds have had cracked the integument was performed and the imbibition in gibberellic acid GA3 500 mgL-1 for 24 h in environmental chamber with temperature adjusted to 30 ºC. The seeds were sown in plastic bags of ± 600 cm3 containing soil + sand + manure in the ratio of 1:1:1. Were evaluated the following attributes: emergence (E), emergence speed index (IVE), root length (CR), diameter of base (DC), shoot length of the aerial part (CPA), fresh mass of the root system (MFSR), fresh mass of the aerial part (MFPA), dry mass of the root system (MSSR) and dry mass of the aerial part (MSPA). Higher values of emergency were obtained intact seeds (30%) and cracked seeds (33%). The germination is stimulated by GA3, reaching 97% in emergency when immersion is for 24 hours in the shade with two screens. The highest values of IQD were obtained in the full sun and minors in shading with two shade screens. It was observed that the roots havechanged their color of whitish for yellowish-white of the 14th to the 21th day after sowing. The hypocotyl, in the early stages has reddish color passing to the green on 14th day after sowing elapsed. The other organs showed no considerable changes. However, biometrically, all organs had an increase in its dimensions, according to in the progression of development. With the exception of CPA and MFSR, it was found spatial dependence for the other studied variables: E, IVE, CR, DC, MFPA, MSSR e MSPA; with range varying of 14,0 a 47,5 m, being the lowest range for the CR and longer range and IDE for the IVE